1994
DOI: 10.1084/jem.179.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are essential for early anti-Listeria defense in the liver, but not in the spleen or peritoneal cavity, as revealed by a granulocyte-depleting monoclonal antibody.

Abstract: SummaryThis study shows that in mice selectively depleted of neutrophils by treatment with a monoclonal antibody, RB6-8C5, listeriosis is severely exacerbated in the liver, but not in the spleen or peritoneal cavity during the crucial first day of infection. At sites of infection in the livers of neutrophildepleted mice, Listeria monocytogenes grew to large numbers inside hepatocytes. By contrast, in the livers of normal mice neutrophils rapidly accumulated at infectious loci and this was associated with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
292
3
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(314 citation statements)
references
References 22 publications
16
292
3
3
Order By: Relevance
“…3A). Consistent with previous findings [7,66,67], CFU in the liver of a-GalCeruntreated mice were significantly increased by Gr-1 1 cell depletion (Fig. 3B).…”
Section: Monocytogenes-induced Inflammation In the Liver And Spleesupporting
confidence: 92%
See 2 more Smart Citations
“…3A). Consistent with previous findings [7,66,67], CFU in the liver of a-GalCeruntreated mice were significantly increased by Gr-1 1 cell depletion (Fig. 3B).…”
Section: Monocytogenes-induced Inflammation In the Liver And Spleesupporting
confidence: 92%
“…After L. monocytogenes infection, numbers of CD11b 1 Gr-1 1 cells in the liver of mice treated with a-GalCer were markedly lower than those of mice left untreated or treated with vehicle. Since (i) a-GalCer treatment numerically increased liver CD11b 1 Gr-1 1 cells and (ii) CD11b 1 Gr-1 1 cells, in particular neutrophils, play a central role as a first line of defense against L. monocytogenes infection [6][7][8], we consider it likely that most of bacteria residing in the liver were eliminated by CD11b 1 Gr-1 1 cells stimulated by a-GalCer treatment prior to infection. Under pathologic conditions, Gr-1 1 cells may injure normal tissue by releasing reactive oxygen intermediates, toxic cationic proteins, and degradative enzymes [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In immunocompetent mice, intravenous injection of a small number of L. monocytogenes causes an acute infection of spleen and liver that is cleared within 7 to 8 days [2,3]. Neutrophils and monocytes are rapidly recruited to sites of bacterial infection and are required for initial control of L. monocytogenes infection [4,5]. Interestingly, in the infected spleen, live L. monocytogenes are mostly found in T cell zones of the white pulp [6].…”
Section: Introductionmentioning
confidence: 99%
“…Using markers specific for B cells (CD20) and T cells (CD3), we demonstrated that these specialized cells of the adaptive immune response are not part of granulomas in listeriosis but are almost exclusively located in between granulomas. Since macrophages and neutrophils are known to play major roles in systemic listeriosis in murine models (8,25,26), we next assessed expression of CD15 (granulocyte marker) (27) and CD68 (macrophage marker) (28) in infected tissues ( Figure 1A). Within the center of the granulomas, basically all cells were CD15 + granulocytes, with only a few CD68 + macrophages.…”
Section: Ido + Dcs Are a Major Component Of Granulomas In Listeriosismentioning
confidence: 99%